Orientacje sprawcze i wspólnotowe współczesnej młodzieży - Peret-Drążewska, Paulina (Wydział Studiów Edukacyjnych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
The primary aim of the article is a discussion on the youth's orientation in the social aspects of life in theoretical and empirical perspective. The research subject raised in this article is to show the image of the today’s youths from the perspective of peers by the designation of some aspects, especially social orientations, that are being only fragments of the necessary conditions to seize the situation of young people.
Causative and Community Orientations of Contemporary Youths
Keywords: social orientations; youths; globalization